Candidial Infection in Pre- Term Babies- A Clinical Study - Venkatesh G; Arun Kumar P (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Invasive candidiasis in neonates is a serious and common cause oflate onset sepsis and has a high mortality. The present study was conducted to assess candidial infection in pre- term babies.Subject and Method:The present study was conducted in the Department of Neonatology. It comprised of 56 low birth weight babies of both genders. In all cases, gestational age, birth weight, length of stay before candidemia, presence of CVC, stay in NICU ? 7 days and mechanical ventilation was recorded. Result:Out of 56 patients, boys were 32 and girls were 24. Gestational age (weeks) was 30.2, birth weight was 1214.5 grams, length of stay before candidemia was 10.2 days, presence of CVC in 54, stay in NICU ? 7 days was seen in 52 and mechanical ventilation was seen in 47. Clinical manifestations was candida endophthalmitis in 13, candida endocarditis in 16 and congenital cutaneous candidiasis in 27. The difference was significant (P< 0.05). Conclusion:Authors found that Candidial infection is common in newborn. Clinical manifestations were candida endophthalmitis, candida endocarditis and congenital cutaneous candidiasis.